Two new HLA class I alleles described in a Spanish individual, HLA‐A*11:01:01:04 and HLA‐B*35:330. (23rd February 2017) - Pacho, A.; Arrieta, A.; Balas, A.; De Juan, M. D.; Vicario, J. L.
Abstract : Two new HLA class I alleles, HLA‐A*11:01:01:04 and HLA‐B*35:330, were characterized in a Spanish patient.